Acquired Syphilis: epidemiological profile of cases in state of Pará from 2017 to 2019 - Bianca Sousa de Almeida Neves; Mariana Bastos Amanajás; Carla Andréa Avelar Pires (Hospital de Clínicas de Itajubá, 2021)
Objective: To quantify patients diagnosed with acquired syphilis and the prevalence of the disease in the state of Pará, Brazil, from January 2017 to June 2019, in addition to characterizing the demographic aspects of patients included in the sample. Methods: observational, descriptive and cross-sectional study, conducted by reviewing the database of the Notifiable Diseases Information System made available by the State Health Department of Pará, of reported cases of acquired syphilis, in the defined period. This study included patients of both sexes, aged 18 years or older, who had acquired syphilis and were notified. Results: 5,620 cases of acquired syphilis were reported, of which the majority were male (n = 3,229; 57.45%), mixed race (n = 4,058; 72.2%), low education (n = 2,250; 40%) and in the young adult range (18-30 years; n = 2,514; 44.74%). The highest concentration of cases was observed in the metropolitan mesoregion of Belém and the Lower Amazon. Conclusions: Acquired syphilis is still prevalent and is characterized as a public health problem. Epidemiological surveillance needs to be constant, and more efficient public policies need to be employed in primary care to reduce the number of cases and make early diagnoses with appropriate treatment.